On the presentation and placement of collocations in monolingual English learners’ dictionaries: Insights into encoding and retention - Dziemianko, Anna (My University, 2014)
The paper reports on an empirical investigation in which the effect of lexicographic presentation and positioning of collocations on encoding and retention was analysed. Two places of collocations in entries (entry-initial and entry-final) in three presentation conditions (box, bold before examples, bold within examples) were taken into consid- eration. The experiment centred on verb+noun collocations and was conducted among a large group of non-native speakers of English at the intermediate level. The results show that the presentation and place of collocations significantly affected their use. Remembering collocations, in turn, proved to be conditioned by the adopted mode of presentation, but not by their distribution in the entry. The paper ends with suggestions for optimizing the presentation of collocations depending on their position in the micro- structure. The investigation does not prove the usefulness of collocation boxes.
Keywords: collocations; dictionary; encoding; retention